The Cranky Thermometers: Visual analogue scales measuring irritability in youth. (2nd March 2018) - Melvin, Glenn A.; Tonge, Bruce J.; Mulraney, Melissa; Gordon, Michael; Taffe, John; Klimkeit, Ester
ABSTRACT: This study assessed the psychometric properties of two visual analogue scales of irritability, known as the Cranky Thermometers (CT), in both an Australian community secondary‐school sample (N = 164) and a sample of adolescents with a depressive disorder (N = 127). The first scale Cranky Now measures current irritability, and the second, Cranky Two Weeks, measures peak irritability within the last two weeks. CT scores were significantly higher in adolescents with major depressive disorder than in the school sample and showed improvement following treatment for depression. Positive associations were found between CT and irritability scores as determined by Kiddie Schedule for Affective Disorders and Schizophrenia (not irritable, sub‐threshold, threshold irritability) and Affective Reactivity Index scores. Results suggest that the CTs are rapidly administered, have promising psychometric properties and demonstrate utility in measuring irritability in clinical and community settings.